A PELATIHAN PENDAMPINGAN GOOGLE BISNISKU DAN SAHABAT UMKM BAGI PARA PELAKU USAHA UMKM DI DESA SEBEWE : PELATIHAN PENDAMPINGAN GOOGLE BISNISKU DAN SAHABAT UMKM BAGI PARA PELAKU USAHA UMKM DI DESA SEBEWE - edi edi; Hanifa Sri Nuryani; Abdul Salam; Hartini; Fahlia; Fadli Faturrahman (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This community empowerment activity was carried out in Sebewe Village, North Moyo District, Sumbawa Regency. Based on the results of community service activities with the theme "Training Assistance for Google Bisnisku and Sahabat UMKM to Improve Marketing in the Digital Era for Small and Medium Business Actors in Sebewe Village, North Moyo District" that have been carried out, it can be concluded as follows: 1) Participants already have additional marketing information through online media and how to use it to market the products of small and medium businesses in Sebewe Village through Google Bisnisku and Sahabat UMKM. 2) The participants of small and medium businesses get a management technique method for marketing products through online media. Small and medium businesses in Sebewe Village know how to do simple bookkeeping